NPI-0052 and gamma-radiation induce a synergistic apoptotic effect in the most aggressive medulloblastoma subgroup. (12th October 2019) - Frisira, Eleni; Rashid, Fatima; Michod, David; Victoria Niklison Chirou, Maria
Abstract: Group 3 medulloblastoma (MB) is the most aggressive and least characterised of all MB subgroups. These tumours are highly metastatic and patients undergo aggressive treatments leaving survivors with severe side effects. The standard of care for these patients consists of surgical resection followed by gamma-radiation and chemotherapy. Whilst this conventional therapy is successful in the majority of cases, however, many survivors are left with lifelong severe neurocognitive and physical sequelae. Interestingly, the proteasome plays a vital role in the pathogenesis of different tumours, therefore proteasome inhibition can be used as a new strategy for treating MB. NPI-0052 is a proteasome inhibitor that can penetrate the blood-brain barrier with a good safety profile, making it an appealing treatment for brain tumors. In the present study, we evaluate the anticancer activity of NPI-0052 in a range of MB patient derived MB cells and cell lines. Our preclinical work demonstrated that NPI-0052 can inhibit proteasome activity and activate apoptosis in MB cells. We also show that the p53-family plays a substantial role in NPI-0052's mechanism of action. Moreover, we observe that NPI-0052 has a synergistic apoptotic effect with gamma-radiation, a component of the current MB therapy, in both cells and tumour organoids. Our work underscores the use of NPI-0052 as a novel therapy for reducing the doses of gamma-radiation in G3-MB patients.